2018
DOI: 10.1016/j.immuni.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

An Interleukin-23-Interleukin-22 Axis Regulates Intestinal Microbial Homeostasis to Protect from Diet-Induced Atherosclerosis

Abstract: Summary While commensal flora is involved in the regulation of immunity, the interplay between cytokine signaling and microbiota in atherosclerosis remains unknown. We found that interleukin (IL)-23 and its downstream target IL-22 restricted atherosclerosis by repressing pro-atherogenic microbiota. Inactivation of IL-23-IL-22 signaling led to deterioration of the intestinal barrier, dysbiosis and expansion of pathogenic bacteria with distinct biosynthetic and metabolic properties, causing systemic increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
111
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 56 publications
1
111
0
2
Order By: Relevance
“…A separate group described IL-22–deficient mice with less bacterial diversity and decreased abundance of Lactobacillus , but increased abundance of Escherichia , Salmonella , and Helicobacter , that showed increased susceptibility to dextran sulfate sodium (DSS) colitis in cohoused wild-type animals, indicating that IL-22–deficient animals can harbor microbiota with transferable effects on barrier function (Zenewicz et al, 2013). The defective barrier and increased inflammation in IL-23R knockout and IL-22 knockout mice increase the systemic level of lipopolysaccharide and trimethylamine N -oxide, which lead to increased diet-induced atherosclerosis and alcohol-induced hepatitis (Fatkhullina et al, 2018).…”
Section: Role Of Il-22 In Antimicrobial Defense and Dysbiosismentioning
confidence: 99%
“…A separate group described IL-22–deficient mice with less bacterial diversity and decreased abundance of Lactobacillus , but increased abundance of Escherichia , Salmonella , and Helicobacter , that showed increased susceptibility to dextran sulfate sodium (DSS) colitis in cohoused wild-type animals, indicating that IL-22–deficient animals can harbor microbiota with transferable effects on barrier function (Zenewicz et al, 2013). The defective barrier and increased inflammation in IL-23R knockout and IL-22 knockout mice increase the systemic level of lipopolysaccharide and trimethylamine N -oxide, which lead to increased diet-induced atherosclerosis and alcohol-induced hepatitis (Fatkhullina et al, 2018).…”
Section: Role Of Il-22 In Antimicrobial Defense and Dysbiosismentioning
confidence: 99%
“…Induce and promote th17 differentiation IL-27 alone has no apparent stimulatory properties, collaboration with other ILs promote or inhibit T cell differentiation and proliferation Promote Treg activity, suppress the Teff cell (Th1, and Th17 ) activity Ma and Trinchieri, 2001;Kastelein et al, 2007;Collison and Vignali, 2008;Vignali et al, 2008;Cox et al, 2011;Vignali and Kuchroo, 2012;Wojno and Hunter, 2012;Sun et al, 2015 Regulation of inflammation Except inflammatory environment induced by DOX or Ang II, all play pro-inflammatory role Always play a proinflammatory roles, no anti-inflammatory effects had been reported Not only play an anti-inflammatory role, but also play a proinflammatory effects, may be associated with inflammatory microenvironment Always relieves the inflammatory response Davenport and Tipping, 2003;Vignali and Kuchroo, 2012;Jin et al, 2012;Koltsova et al, 2012;Li et al, 2012;Yan et al, 2012;Jääskeläinen et al, 2013;Abbas et al, 2015;Subramanian et al, 2015;Sun et al, 2015;Andrews et al, 2016;Tao et al, 2016;Hu et al, 2016;Gregersen et al, 2017;Fatkhullina et al, 2018;Ye et al, 2018b;Jia et al, 2019;Liu et al, 2019;Vargas-Alarcón et al, 2019;Ye et al, 2019 family members have significantly higher levels of expression in patients with atherosclerosis and coronary artery disease, and are closely related to the progression of these diseases.…”
Section: Induce Th1 and Mø1 Differentiationmentioning
confidence: 99%
“…Another study reported that there was no significant difference in atherosclerotic area between low-density lipoprotein receptor (LDLR) knockout mice and IL-23 + LDLR double-knockout mice, after they were all fed with high-fat diet (Engelbertsen et al, 2018). A recent study reported that deficiency of IL-23 significantly decreased IL-22 expression in ApoE-knockout mice, and also reduced expression of IL-22, thereby relieving the release of inflammatory substances, and thus alleviating the process of atherosclerosis (Fatkhullina et al, 2018). Subramanian et al reported that granulocyte-macrophage colony stimulating factor (GM-CSF) up-regulates the expression of IL-23, which further promotes the differentiation of macrophages and atherosclerosis development (Subramanian et al, 2015).…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the numbers are small and the duration of the study is still too short to attribute reduction of atherosclerotic plaque formation to IL‐23 inhibition, together these results may be hypothesis generating towards whether guselkumab might reduce the risk of MACEs in patients with psoriasis; however, larger prospective studies are needed to demonstrate this. On the other hand, IL‐23 inhibition may interfere with intestinal microbial homeostasis, subsequently increasing proatherogenic metabolites, contributing to atherosclerosis . It is clear that a more complete understanding of the downstream effects of IL‐23 inhibition is necessary.…”
mentioning
confidence: 99%